Reliability, Validity and Factor Structure of the GHQ-28 in Iranian Elderly - Seyed Kazem Malekooti; Arash Mirabzadeh; Paridokht Fathollahi; Mozhde Salavati; Shamsodin Kahali; Azize Afkham Ebrahimi; Taher Zandi (University of Social Welfare & Rehabilitation Sciences, 2006)
Objectives: Given the increasing trend of old population even in the developing countries, mental disorders of elderly are public health problems in these countries. Access to valid and reliable screening instruments is needed for conducting community surveys and clinical trials. The main objective of this study is to provide the Iranian version of the General Health Questionnaire-28 (GHQ) in old people. Methods & Materials: The GHQ-28 Persian version was developed by translation and back translation. 204, subjects 59 years or older, who were chosen randomly from residents of Ekbatan, district of Tehran, the capital city of Iran, completed the GHQ-28 Composite International Diagnostic Interview (CIDI) was used to establish a gold standard diagnosis of major depressive disorders. Results: GHQ-28 was found to be an internally consistent measure. Alpha, split-half coefficients and test-retest reliability were 0/94, 0/86 and 0/6 respectively. Four factors were extracted by using factor analysis and the principle component analysis (varimax rotation): "depression, anxiety, somatic symptoms, social function". Using Receiver Operating Curve (ROC) analysis, the ptimum cutoff score for GHQ-28 is 19/20, yielding a sensitivity of 0/83 and a specificity of 0/76. GH0-28 was derived from a long form. Conclusion: The long and short forms of GHQ have excellent properties as screening instruments for mental disorders in older dwellers in Iran, particularly in urban areas, as presented in our finding.